X-Ray Scanning Reduce Soluble Active Molecules of Mesenchymal Stem Cells - Putra, Agung; Pasongka, Zenitalia; Widyatmoko, Agus; Prasetio, Ardi; Dirja, Bayu Tirta (International Journal of Cell and Biomedical Science, 2022)
Mesenchymal Stem Cells secrete various anti-inflammatory and regenerative SAMs-MSCs that possess immunomodulatory properties and may accelerate wound healing. As a potential agent for therapeutic, SAMs-MSCs should be stable in any condition, including under X-Ray Scanning. The previous study reveal that X-Ray Scanning may induce protein damage. However, the investigation regarding the stability of SAMs-MSCs under X-Ray Scanning is limited, thus this study aimed to investigate the stability of SAMs-MSCs after X-Ray Scanning. Mesenchymal Stem Cell medium was filtrated using the TFF method at 300 and 5 kDa filter cut off and sterilized using 0,1 um syringe. The SAMs-MSCs underwent X-ray Scanning using public Air Port X-Ray twice. The SAMs-MSCs concentration was measured using ELISA. T-test analysis was performed for the statistical analysis with P<0,05. This study revealed that X-ray scanning reduce the concentration of SAMs-MSC. A previous study found that x-ray irradiation may damage protein at 6–18 keV caused by the energy deposited by photoelectrons that are generated by the interaction of X-ray photons and the protein leading to photoelectron-induced damage.